Prognostic impact of the level of nodal involvement: retrospective analysis of patients with advanced oral squamous cell carcinoma. Issue 1 (January 2017) - Murakami, R.; Nakayama, H.; Semba, A.; Hiraki, A.; Nagata, M.; Kawahara, K.; Shiraishi, S.; Hirai, T.; Uozumi, H.; Yamashita, Y.
Abstract: We retrospectively evaluated the prognostic impact of the level of nodal involvement in patients with advanced oral squamous cell carcinoma (SCC). Between 2005 and 2010, 105 patients with clinical stage III or IV oral SCC had chemoradiotherapy preoperatively. Clinical (cN) and pathological nodal (pN) involvement was primarily at levels Ib and II. We defined nodal involvement at levels Ia and III–V as anterior and inferior extensions, respectively, and recorded such findings as extensive. With respect to pretreatment variables (age, clinical stage, clinical findings of the primary tumour, and nodal findings), univariate analysis showed that extensive cN was the only significant factor for overall survival (hazard ratio [HR], 3.27; 95% CI 1.50 to 7.13; p = 0.001). Univariate analysis showed that all pN findings, including the nodal classification (invaded nodes, multiple, and contralateral) and extensive involvement were significant, and multivariate analysis confirmed that extensive pN (HR 4.71; 95% CI 1.85 to 11.97; p = 0.001) and multiple pN (HR 2.59; 95% CI 1.10 to 6.09; p = 0.029) were independent predictors of overall survival. Assessment based on the level of invaded neck nodes may be a better predictor of survival than the current nodal classification.